Microbe - Michele Swanson (ASM Press, 2016)
Microbe, 2e brings the excitement, breadth and power of the modern microbial sciences to students and scientists in a fun and engaging way, building on key concepts and skills identified in the Curriculum Guidelines by the American Society for Microbiology Education Board. Intended for microbiology course for majors and pre-health professionals